APOPTOSIS INDUCING EFFECT OF SILVER NANOPARTICLES SYNTHESIZED USING MAGNOLIA CHAMPACA LEAF EXTRACT ON MCF-7 CELL LINE - ANTONY, ANNA; SHRIVASTAV, NEHA; DUBEY, SIDDHARTH; ACHARYA, ASHUTOSH (International Journal of Current Pharmaceutical Research, 2021)
Objective: To synthesize silver nanoparticle (AgNP) using the ethanolic leaf extract of Magnolia champaca (MC-AgNP) and to evaluate its cytotoxicity and apoptotic activity in MCF-7 cell line, and to analyse active Caspase-3 expression in inducing apoptosis. Methods: AgNP was green synthesized using ethanolic leaf extract of MC. Shape and size were analysed by SEM and particle size analyser. Cytotoxicity was tested to find IC50 value. Apoptosis was explored by mitochondrial membrane potential (ΔΨm) assay and active Caspase-3 expression study using flow cytometry. Results: AgNP synthesized was observed to be in spherical shape through SEM micrograph with 164.6 nm in size. IC50 value of 15.90 µg/ml was obtained after 24 h of drug treatment. Changes in ΔΨm and positive active Caspase-3 protein expression were observed. Conclusion: The present results suggest that MC-AgNP has potential anticancer property and also induced cell death via apoptosis through caspase dependent pathway in MCF-7 cells.